PURCHASE SATISFACTION MEDIATES PROMOTION STRATEGY TOWARDS REPURCHASE INTENTION RESELLER IN BETENG TRADE CENTER SURAKARTA FASHION STORE - Hanggun Fatmala Muflaifah; Bambang Mursito; Siti Maryam (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to determine the effect of repurchase intention in terms of promotional strategies and reseller purchase satisfaction at the Beteng Trade Center Surakarta fashion store. This type of research is descriptive quantitative. This study uses primary data collected using a questionnaire as a research instrument. The sample research method used was purposive sampling technique. The respondents of this research were 100 respondents. The data analysis technique used is path analysis. The results of the research in this study can be concluded that promotion strategy has no positive and significant effect on repurchase intention, promotion strategy has a positive and significant effect on purchase satisfaction, purchase satisfaction has a positive and significant effect on repurchase intention, promotion strategy has a positive and significant effect on repurchase. intention through purchase satisfaction. Keywords: Promotion strategy, purchase satisfaction, repurchase intention